Opposition subnational strongholds in dominant party authoritarian regimes (DPARS) : the Pakatan coalition in Selangor and Penang from 2008 to 2018 - Yeoh, Tricia (2022)
Opposition parties within dominant party authoritarian regimes (DPARs) operate under challenging conditions as they are systematically deprived of resources. Yet in some cases, opposition parties have performed surprisingly well at the subnational level, against the odds. This thesis addresses two central questions. First, under what conditions can opposition parties achieve political party institutionalisation and establish subnational strongholds within DPARs? Second, what strategies and methods do these opposition parties employ to do so?